Selected point scales used in geriatric assessment of the patient’s condition - Biercewicz, Monika (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2019)
Introduction Comprehensive Geriatric Assessment (CGA) is a fundamental principle of geriatrics management aimed at limiting dysfunctions in the elderly. It is a multidirectional, integrated diagnostic process necessary for the biopsychological assessment of an elderly person in a home or institutional environment. Aim The aim of this study is to present the most commonly used standardized tools to facilitate the assessment of the functional, mental and social state of elderly patients, used in the overall diagnostic process, which is a comprehensive geriatric assessment. Overview The point scales used in the comprehensive geriatric assessment (CGA) can be divided into 4 large groups, i.e. scales assessing physical health (Clinical/Outcome Assessment), scales assessing functional status (Acti¬vities of Daily Living), scales assessing mental state (Cognitive and Mental Assessment) and scales assessing the socio-environmental situation (state) of the respondent (Global Assessment/Quality of Life). Conclusions The presented point scales can be successfully used both in inpatient care (hospital wards) and in long-term care facilities (care and treatment centers, rehabilitation departments, nursing homes for chronically ill pa¬tients, etc.) and in open care, as well as in the practice of a physician and family nurse.